HUBUNGAN BEBAN KERJA FISIK DAN BEBAN KERJA MENTAL DENGAN KELELAHAN KERJA PADA PEKERJA DI PT.X SURAKARTA - Fathonah, Okisa Putri Nur; Nisa, Farhana Syahrotun; Chahyadhi, Bachtiar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
ABSTRACTWork fatigue is the body's defense mechanism designed to avoid the body from overharm possibilites. Fatigue is characterized by a shift in both physical and mental state that lowers one's capacity for and endurance during work. It was established from the initial survey that 5 employees (or 50%) had moderate category fatigue and 5 employees (or 50%) had severe category fatigue. The purpose of this study was to ascertain the link between work tiredness and both physical and mental burden. A cross sectional analytic observational research design was adopted by for this study, and simple random sampling was used for the sampling method. The total sample population of this study are 87 workers. The NASA-TLX questionnaire, a reaction timer, and the 10-beat method of measuring pulse were all employed in this study. The Somers' test and the ordinal logistic regression test were employed as data analysis approaches. The findings of the bivariate analysis using the Somers'd test revealed a significant association between physical workload and work fatigue with a p-value of 0.000. According to the findings of the multivariate study, physical workload had a 7,028 times greater impact on job fatigue.